Increase in the number of patients diagnosed using the new classification of hypertensive disorders of pregnancy in Japan. Issue 6 (28th March 2019) - Mayama, Michinori; Morikawa, Mamoru; Umazume, Takeshi; Nakagawa, Kinuko; Hosokawa, Ami; Yamaguchi, Masahiro; Chiba, Kentaro; Kawaguchi, Satoshi; Watari, Hidemichi
Abstract: Aim: This study aimed to examine how the number of patients diagnosed with pre‐eclampsia increased according to the Japanese classification of hypertensive disorders of pregnancy (HDP) that was revised in 2018. The effect of new classification on perinatal outcomes was also analyzed. Methods: We enrolled 181 women with HDP who delivered at Hokkaido University Hospital between February 2011 and December 2017. All women were reclassified on the basis of the new classification, in which proteinuria was not required to diagnose pre‐eclampsia in patients with maternal organ damage. The number and reasons of reclassification and the admission rate to the neonatal intensive care unit (NICU) and gestational age (GA) at the onset of HDP and at delivery were analyzed. Results: In this cohort, 17 (9.4%) of 181 women with HDP were reclassified. Low platelet count (41.2%) and uteroplacental dysfunction (41.2%) were the two main causes for reclassification. GA at the onset of HDP (33.6 [29.9–36.1] weeks vs 37.4 [35.7–38.4] weeks; P  < 0.001) and at delivery (35.9 [32.4–37.3] weeks vs 38.1 [37.3–39.6] weeks; P  < 0.001) were significantly earlier in women with reclassification than women without reclassification. The NICU admission rate was higher in women with reclassification than women without reclassification (70.6% vs 20.4%; P  < 0.001). Conclusion: Almost 10% of pregnant women were newly diagnosed with pre‐eclampsia as per the new Japanese classification of HDP. Women with reclassification as pre‐eclampsia had a greater risk of preterm delivery and NICU admission than those who were not reclassified.